Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.